MANAJEMEN PENGEMBANGAN SUMBER DAYA MANUSIA DI SEKOLAH - ASTUTI Astuti (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2018)
Abstract. Human Resource Management (HRM) is all activities related to the recognition of the importance of educators and education personnel in schools as vital human resources, which contribute to school goals, and utilize functions and activities that ensure that human resources are used effectively and fair for the benefit of individuals, schools and communities. Human resource management aims to formulate the needs of educators and education personnel, develop and empower educators and education personnel to obtain the optimal value of benefits for individual educators and education personnel concerned. The scope of management of human resources in schools is HR Planning, analysis of educators and education personnel, procurement of educators and education personnel, selection of educators and education personnel, orientation, placement and assignment, compensation, performance assessment, career development, training and personnel development educators and the creation of work life quality, educator and education power negotiations, research of educators and education personnel, pensions and dismissal of teaching and education personnel. Keywords: Human Resource Development Management